Analyzing Speaking Challenges Faced by Introverted Student Teachers in Teaching: A Study at English Language and Literature Department - Hafidz, Ahmad; Sari, Senorica Yulia (Universitas Negeri Padang, 2025)
This study aimed to explore the speaking challenges faced by introverted student teachers in the English Language and Literature Department at Universitas Negeri Padang. The focus was on three main categories of challenges: linguistic, psychological, and environmental. This research used a quantitative approach with a survey design. The data were collected through a questionnaire that included closed-ended questions to identify the main challenges and open-ended questions to support the findings. A total of 30 introverted student teachers participated in the study. The results showed that in the linguistic category, fluency was the most common challenge. However, in the psychological category, the fear of making mistakes while speaking was the biggest problem. Furthermore, in the environmental category, the limited use of English in daily life became the main obstacle. These challenges often caused introverted student teachers to feel nervous, less confident, and unprepared when speaking in front of others. The findings suggested that more support should be given to introverted student teachers by creating a more comfortable classroom environment, providing structured speaking activities, and encouraging regular English use. These efforts could help improve their speaking confidence and teaching performance.